2016
DOI: 10.1002/elsc.201600073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating feeding strategies for microbial oil production from glycerol by Rhodotorula glutinis

Abstract: Oil production, from biodiesel by‐product glycerol, through microbial fermentation provides a promising option as part of an integrated biorefinery process. However, bioprocessing improvements are required to make the process more efficient. In the present work, different glycerol feeding strategies were evaluated under fed‐batch cultivation of the oleaginous yeast Rhodotorula glutinis. Results showed that the concept of targeting first a cell proliferation stage and then a lipid accumulation stage had benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 46 publications
1
17
0
2
Order By: Relevance
“…, ; Karamerou et al . ). It is evident that as far as the synthesis of SCO that is aimed to be transformed in second‐generation biodiesel is concerned, only hydrophilic carbon sources (i.e.…”
Section: Oleaginous Micro‐organismsmentioning
confidence: 97%
See 2 more Smart Citations
“…, ; Karamerou et al . ). It is evident that as far as the synthesis of SCO that is aimed to be transformed in second‐generation biodiesel is concerned, only hydrophilic carbon sources (i.e.…”
Section: Oleaginous Micro‐organismsmentioning
confidence: 97%
“…; Karamerou et al . ). On the other hand, given that it was desirable to elucidate this ‘interplay’ between the synthesis of storage lipid and citric acid on media enabling the de novo lipid accumulation in Y. lipolytica , it has recently been demonstrated that cultivation of this yeast strain on double‐limited media (i.e.…”
Section: Physiology Of Lipid Accumulation Processmentioning
confidence: 97%
See 1 more Smart Citation
“…Among others the microbial production of 1,3‐propanediol (PDO) and n ‐butanol has received particular attention and is industrially used . They can be produced from fermentations of glycerol – a byproduct from biodiesel production ‐ and sugars, e.g. using Clostridia .…”
Section: Introductionmentioning
confidence: 99%
“…Among others the microbial production of 1,3-propanediol (PDO) and n-butanol has received particular attention and is industrially used [1][2][3][4][5][6][7][8]. They can Abbreviations: C. pasteurianum, Clostridium pasteurianum; PDO, 1,3-propanediol; gRNA, guide RNA; MFA, metabolic flux analysis; SNPs, single-nucleotide polymorphisms be produced from fermentations of glycerol -a byproduct from biodiesel production [9][10][11] -and sugars, e.g. using Clostridia [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%